A Patient with Recurrent Hypokalaemia - Bala, Chandra Shekhar; Reza, Ishrat; Momen, Md A Basit Ibne; Ahasan, HAM Nazmul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2016; 34(4): 228-230